A STUDY OF BEHDINI-KURDISH CHILDREN’S LANGUAGE AFFECTED BY YOUTUBE ENGLISH VIDEOS - Dilkhosh, Soleen; Malo, Sanan (Humanities Journal of University of Zakho, 2025)
This study aims to investigate how YouTube videos in English affect the vocabulary development of Behdini Kurdish children in Zakho, Kurdistan Region-Iraq, addressing concerns about technology’s impact on first language preservation. Three main questions are investigated in the study: What is the relationship between Behdini Kurdish and English-language YouTube videos among youngsters in Zakho? What impact does YouTube have on kids’ language development? Does children’s preference for L1 vocabulary over L2 vocabulary change as a result of watching English-language YouTube videos? Using a mixed-methods cross-sectional approach, five Kurdish children from Zakho, ages three to six, participated. A picture-based vocabulary recognition test with 20 commonplace items and a parental questionnaire evaluating language use patterns and YouTube viewing habits were used for data collecting. Participants were divided into three groups based on how much time they spent on YouTube each day: low (1-2 hours), medium (2-3 hours), and high (3+ hours). Children’s unplanned reactions to word stimuli were recorded on audio, then transcribed and subjected to correlation analysis and descriptive statistics. The results indicated a significant correlation between the amount of time spent on YouTube and preferred English vocabulary. Children with high exposure (60 percent of participants) demonstrated 90% English word memory compared to just 10% Kurdish recall, with a mean preference score of 1.10 (where 1 = English and 2 = Kurdish). English was favored 79% of the time by those with medium expertise and 65% of the time by those with little exposure. Younger children (3–4 years) preferred English more than older children (11.8), with a mean score of 14.2, indicating higher receptivity during critical periods of language development. These results imply that while prolonged exposure to YouTube promotes L2 acquisition, it may jeopardize L1 preservation in minority language environments. In order to protect Kurdish linguistic heritage and promote multilingual development in young children, the study suggests using parental mediation and balanced language exposure techniques. This study advances our knowledge of how native language preservation in multilingual societies is impacted by digital media.